Japanese Clause Relativization Strategy - Pradhana, Ngurah Indra; Udayana, I Nyoman; Artawa, Ketut; Purnawati, Ketut Widya (RIRAI Publisher, 2025)
This study is entitled Japanese Clause Relativization Strategy. The purpose of this study is to describe the structure, strategy, and previous functions of relative clauses in Japanese. The theory used in analyzing the formulation of problems related to relative clauses in this study refers to the theory developed by Dixon (2010) in his book entitled